Trends in Residential Building Materials in the State of Victoria. Issue 4 (1st November 2022) - Paton-Cole, V; Crawford, R H; Turnbull, R; Fitzgerald, E; Michalewicz, A; Garber, J
Abstract: As the population in Victoria continues to grow, there has been a corresponding increase in building approvals across the State. Houses characterised as low-rise residential buildings often take the largest share of these approvals, with incessant residential building activities being driven by record low interest rates. Low-rise residential buildings comprise various building forms that use a number of specified construction materials to construct the building envelope and other structural and non-structural elements. As materials used for constructing residential building envelopes continue to evolve, these materials must be fit for purpose, and satisfy design criteria and performance requirements, while being aesthetically pleasing. This research analyses the trend in construction materials used in building envelopes of low-rise residential buildings using data from building permits issued between 1996 to 2019. The trend analysis shows that traditional double brick wall systems and suspended timber floors have reduced in popularity for houses built in the 21st century. The analysis also shows that brick veneer wall cladding systems built over slab-on-ground footings is the dominant construction form while the roof cladding material is influenced by geographical location. Insights from the data analysis indicate very little innovation has emerged in materials for residential building envelopes despite its crucial role in providing thermal comfort for inhabitants. Results from this research will serve as a basis to provide quantitative assessment of the trend in materials resource; provide insights about the impact of new building envelope products on existing industries; and perspectives on materials for future building envelopes.